Entrepreneurial proposal: an english language training course for the tourism sector in four municipalities of the coffee region (Phase II) (2022)
This entrepreneurial proposal project is intended to create an English language training course to promote the communicative competence and sociocultural awareness of employees from specific businesses in the tourism sector. The extractivist economy that characterizes Colombia attempts to potentiate national tourism as another economic field. For this reason, the Colombian government has offered courses in different national institutions focused on tourism for small businesses and employees in this sector. However, these attempts have been made to potentiate national tourism as another economic field but not as an educational strategy to interact with touristic foreigners through the English language. This project intends to provide specialized English instruction courses for restaurants, travel agencies, hotels, and coffee bars in the following municipalities: Santuario, Anserma, Dosquebradas, and Pereira. These courses will be offered to tourism employees with a maximum of 15 students per group. Each course will aim to achieve a B1.1 level with a duration of 17 weeks(102 hours per course). The design ofthe courses will be focused on collaborative work using real-life situations. This will be carried out through the socio-constructivist theory. In addition, ESP approach (English for Specific Purposes) will play an essential role in the lessons as the target content focuses on what the tourismemployees need in their specific work setting. The expected results are to provide small businesses with the capability to interact with foreign tourists at a basic level and to promote intercultural awareness in order to know how to assertively interact with tourists.